The genus Siderus (Lepidoptera: Lycaenidae) in French Guiana: four newly discovered species and conspicuous male genitalia polymorphism - Faynel, Christophe; Fåhraeus, Christer; Ramirez, Juan-Jose; Robbins, Robert K. (Zootaxa, 2024)
The species of Siderus Kaye present in French Guiana are listed and detailed with notes on male territorial behavior and the plants at which adults feed. In total, seven species were recorded: Siderus leucophaeus (Hübner); Siderus parvinotus Kaye (first record from French Guiana); Siderus athymbra (Hewitson); Siderus diringeri Faynel, Robbins & Fåhraeus sp. nov.; Siderus bisignatus Faynel, Ramírez & Robbins sp. nov.; Siderus castelain Faynel, Fåhraeus & Robbins sp. nov. and Siderus toussaint Faynel, Robbins & Fåhraeus sp. nov. A preliminary delimitation of the genus Siderus is proposed. Description, distribution, detailed illustrations of adults and male genitalia (and some female) are provided for each new species.